Doxycycline speeds up healing of chronic venous ulcers. Issue 2 (5th April 2013) - Serra, Raffaele; Gallelli, Luca; Buffone, Gianluca; Molinari, Vincenzo; Stillitano, Domenico M; Palmieri, Camillo; de Franciscis, Stefano
Abstract: Venous ulcers are common, with an overall prevalence of up to 2% in the general population of western countries, and have significant socioeconomic impact. Matrix metalloproteinases (MMPs) are involved in the alteration of extracellular matrix that could lead to venous ulceration. Sixty‐four patients with venous ulcers were recruited in a 22‐month period. All patients were subjected to the most appropriate treatment considering also the patient's wishes (compression therapy followed or not by vein surgery). Patients were randomised into two groups of 32 persons in each (groups A and B). Patients of group A in addition to the basic treatment, described above, received the administration of oral low doses of doxycycline 20 mg b.i.d. for 3 months, whereas patients of group B received basic treatment only. Healing was assessed by means of direct ulcer tracing with computerised planimetry. Group A showed a higher healing rate compared with group B. In group B, the lower healing rate was related to higher levels of MMP‐9; neutrophil gelatinase‐associated lipocalin and vascular endothelial growth factor, documented in plasma; wound fluid and biopsies executed and compared between both groups. Pharmacological treatments, as doxycycline administration, which by means of its immunomodulatory and anti‐inflammatory actions, through the inhibition of MMP, could improve extracellular matrix functioning and represent a possible solution to support wound healing.